Cardiac surgical aiding for premature infants with patent ductus arteriosus (PDA) in the PerІnatal centre of Autonomous Republic of Crimea - I.A. Aksenova; A.I. Kvasha; B.M. B.M. Todurov; T.U. Babich; A.G. Sidorov; E.V. Borovskaya; P.C. Mihalchevskiy; G.E. Suhareva (Bukovynian State Medical University, 2019)
The analyses of organization aspects and results of surgical treatment of hemodynamic meaningful patent ductus arteriosus (PDA) in premature infants in the III level Perinatal center of Autonomous Republic of Crimea was carried out. PDA is the most frequent reason which complicates the state of newborns with very low and extremely low body weight. Such manifestations need prolonged mechanical respiratory support and medicamental hemodynamic supplementation. The part of infants with PDA needs its surgical closure. From April to July (2013) 9 operation of surgical ligation of the patent ductus arteriosus were performed in the III level Perinatal center of Autonomous Republic of Crimea. Conducted analyzes points at the necessity of early diagnosis and possibility of surgical closure of PDA in newborns in conditions of the III level Perinatal center.